The classification of mild cognitive impairment or healthy ageing improves when including practice effects derived from a semantic verbal fluency task - Felix Dörr; Loris Grandjean; Johannes Tröger; Jessica Peter (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Practice effects are an improvement in task performance with repeated testing. Their absence may indicate compromised learning and may help discriminate healthy from pathological ageing. METHODS We recorded semantic verbal fluency three times in n = 58 healthy older adults or patients with amnestic mild cognitive impairment (MCI) (72.16 ± 4.83 years old, 33 women). We extracted speech features and trained a machine learning classifier on them at each cognitive assessment. We examined which variables were informative for classification and whether they correlated with episodic memory performance. RESULTS We found smaller practice effects in patients with amnestic MCI. There was a 13% improvement in classification performance with features from the third cognitive assessment as compared to the first assessment. Practice effects correlated with episodic memory performance in healthy adults. DISCUSSION Speech features became more informative for classification when repeatedly assessed. They may be a promising tool for identifying individuals at risk of cognitive decline. Highlights In MCI, practice effects in verbal fluency tasks were smaller than in healthy adults. Smaller practice effects in MCI indicated compromised learning. Including practice effects improved the classification of MCI vs. healthy ageing. In MCI, practice effects were independent of episodic memory performance.